Text steganalysis using evolution algorithm approach - Din, Roshidi; Tuan Muda, Tuan Zalizam; Lertkrai, Puriwat; Omar, Mohd Nizam; Amphawan, Angela; Aziz, Fakhrul Anuar (2012)
This study presents a new alternative of steganalysis method in order to detect hidden messages in text steganalysis called Evolution Detection Steganalysis System (EDSS) based on the evolution algorithm approach under Java Genetic Algorithms Package (JGAP). The result of the EDSS can be divided into two groups based on fitness values which are good fitness and bad fitness. Hopefully, this study can produce a good idea to other researchers for understanding the text steganalysis in order to develop a steganalysis system that can contribute a better performance in other domains.